2016
DOI: 10.1002/chem.201600771
|View full text |Cite
|
Sign up to set email alerts
|

α,β‐Double Electrophilic Addition of Allene‐1,3‐Dicarboxylic Esters for the Construction of Polysubstituted Furans by KI/tert‐Butyl Hydroperoxide (TBHP)‐Promoted Oxidative Annulation

Abstract: An unprecedented KI/tert-butyl hydroperoxide promoted tandem Michael addition/oxidative annulation of allene-1,3-dicarboxylic esters and 1,3-dicarbonyl compounds has been developed. This procedure provides a new, facile, and transition-metal-free synthetic approach to afford polysubstituted furans in moderate to excellent yields (up to 93 %). This method first establishes a α,β-double electrophilic reaction mode of allene-1,3-dicarboxylic esters to form 1,3-dicarbonyl compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 62 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…In this regard, transition‐metal‐catalyzed dehydrogenative heterocylization has been used to construct furan‐fused carbocycles or multisubstituted furans . Intramolecular cyclizations involving alkynyl epoxides, allenyl ketones, allenyl or homopropargylic alcohols, vinyl diazoesters, and allene‐1,3‐dicarboxylic esters were employed for the same purpose. Copper‐catalyzed intermolecular heterocyclization of alkynyl ketones and imines, iron‐catalyzed cyclization of 1,6‐enynes, phosphine‐mediated reductive condensation of γ‐acyloxybutynoates, Brønsted acid promoted cyclization of 1,4‐diketones, and palladium‐catalyzed condensation of N‐arylimines and alkynylbenziodoxolones all afforded the corresponding furan derivatives.…”
Section: Figurementioning
confidence: 99%
“…In this regard, transition‐metal‐catalyzed dehydrogenative heterocylization has been used to construct furan‐fused carbocycles or multisubstituted furans . Intramolecular cyclizations involving alkynyl epoxides, allenyl ketones, allenyl or homopropargylic alcohols, vinyl diazoesters, and allene‐1,3‐dicarboxylic esters were employed for the same purpose. Copper‐catalyzed intermolecular heterocyclization of alkynyl ketones and imines, iron‐catalyzed cyclization of 1,6‐enynes, phosphine‐mediated reductive condensation of γ‐acyloxybutynoates, Brønsted acid promoted cyclization of 1,4‐diketones, and palladium‐catalyzed condensation of N‐arylimines and alkynylbenziodoxolones all afforded the corresponding furan derivatives.…”
Section: Figurementioning
confidence: 99%
“…17 Allenes are considered to be crucial building blocks in heterocyclic compounds synthesis due to their unique structures and multiple active sites, [18][19][20][21] which are still the least studied allcarbon unsaturated functional groups. 22,23 Since the discovery of the two classical methods, chemists have developed many groundbreaking methods for the synthesis of tetrasubstituted furans, some of which rely on the annulation of allenes [24][25][26][27][28][29][30][31] (Scheme 1). Despite the availability of the reported methods, there are some limitations.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction of 1m with 2b proceed smoothly to give the corresponding pyrrole 3mb in good yield (80%, Table , entry 1). To our delight, when an unsymmetric allene 2c was employed for this reaction, in contrast to our furan synthesis, the desired product 3mc was obtained in 57% yield with excellent regioselectivity (Table , entry 2). Subtle change of R 4 group of allene to n Bu gave slightly lower yield of 3md with excellent regioselectivity as well (Table , entry 3).…”
mentioning
confidence: 96%
“…For instance, in 1971, Danishefsky and co-workers found that enamines could smoothly react with allenes under alkaline conditions at 100 °C, delivering α-pyridones (Scheme a) . On the other hand, given that the wide applications of allenes for constructing structurally diverse heterocycles, , we have recently developed a novel protocol for the synthesis of polysubstituted furans via KI/TBHP promoted tandem Michael addition/oxidative annulation, in which a novel α,β-double electrophilic addition strategy of allene-1,3-dicarboxylic esters with 1,3-dicarbonyl compounds was first established (Scheme b) . Therefore, as part of our continuous interest in the synthesis of heterocycles, we were wondering whether a similar α,β-double electrophilic addition strategy could be extended to the reaction of allenes with enamines instead of 1,3-dicarbonyl compounds, which would afford pyrroles rather than pyridones.…”
mentioning
confidence: 99%